Gross Domestic Product, BI Rate dan Sesitivitas Kurs Terhadap Return Saham Perusahaan Terindeks LQ45 - Gede Aryawan (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2022)
The research only focuses on non-fundamental factors or systematic factors that affect stock returns of LQ 45 companies listed on the Indonesia Stock Exchange from 2010 to 2020 or for 10 years. The data used to prove the hypothesis of this study were obtained through the osairis database. The analysis technique of this research is multiple linear regression. Based on hypothesis testing of 3 hypotheses, namely GDP, BI Rate and Exchange Sensitivity, only GDP has a positive effect on Stock Return. Another finding of this study is that 2 fundamental factors, namely profit margin and firm size, have no effect on stock returns. The limitations of the research that need to be followed up by subsequent research is to expand the research population at the ASEAN level with a longer year of observation. Subsequent research should explore the BI Rate and Exchange Rate in volatile conditions and consider other fundamental factors.